2013
DOI: 10.1126/scitranslmed.3004682
|View full text |Cite
|
Sign up to set email alerts
|

A Dendritic Cell–Based Vaccine Elicits T Cell Responses Associated with Control of HIV-1 Replication

Abstract: Combination antiretroviral therapy (cART) greatly improves survival and quality of life of HIV-1-infected patients; however, cART must be continued indefinitely to prevent viral rebound and associated disease progression. Inducing HIV-1-specific immune responses with a therapeutic immunization has been proposed to control viral replication after discontinuation of cART as an alternative to "cART for life." We report safety, tolerability, and immunogenicity results associated with a control of viral replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
181
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 192 publications
(191 citation statements)
references
References 29 publications
3
181
1
6
Order By: Relevance
“…This finding, together with that of a recently published study using DC pulsed with autologous virus [7] underscores the central role of DCs in therapeutic vaccination.…”
Section: Discussionmentioning
confidence: 63%
“…This finding, together with that of a recently published study using DC pulsed with autologous virus [7] underscores the central role of DCs in therapeutic vaccination.…”
Section: Discussionmentioning
confidence: 63%
“…They found that this strategy induced a control of pVL similar to that reported by Lu et al 44 and our group. 55 These data suggest that a combination of autologous antigens administered to patients on cART could have a higher virological effect than heterologous immunogens, although it should be tested in a randomized clinical trial.…”
Section: New Designed Immunogens To Pulse Md-dcmentioning
confidence: 96%
“…11,37,38 Some studies in animal models suggest that animals immunized with DCs loaded with HIV-1 viral lysate, envelope glycoproteins or inactivated virus mount a potent immune response against HIV-1. [39][40][41]42 Although it has been performed at least 13 published clinical trials of DC-based immunotherapy for HIV infection in humans [43][44][45][46][47][48][49][50]55 (reviewed in ref. 9), most of them were non-controlled, nonrandomized studies.…”
Section: Clinical Trials With Md-dcbased Therapeutic Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations